Post-Graduation Impact of a Program Planning Service-Learning Project. - Risisky, Deb; Goldson, Tess; DeMezzo, Robert (Pedagog. health promot., 2020)
Research has shown that service-learning can increase student-learning outcomes across various disciplines. Service-learning opportunities have been steadily increasing in college settings, especially in health-related fields. This evaluation of an undergraduate public health course at a mid-size, public university in New England sought to understand the impact of service-learning on material retention, internships, and post-graduation public health careers. A 25-item questionnaire was emailed to students who took the course between the Fall 2010 and Spring 2016 semesters with 75 completed (33.3% completion rate). More than half of the respondents noted that their participation in a service-learning project positively affected their internship experience, their first post-graduation job, and their overall career, while also helping them retain the course material after graduation. Open-ended responses provided insight to the qualitative responses. Respondents noted that in addition to having the understanding and ability to put on programs in their community, they also had more confidence in their abilities. The opportunity to practice public speaking skills as well as work collaboratively in group settings, were both noted as essential skills needed to succeed in the public health workforce. It was concluded the project had a positive impact on student's learning and retention in planning, implementing, and evaluating an actual health promotion program as well as how they were able to use those skills in their careers., (C)2021Sage Publications
3 citations (Crossref) [2023-10-31] Place: (C)2021Sage Publications
Keywords: dept.fye; dept.pch; dept.rslf; health education; peer-reviewed; program planning; service-learning